Pengaruh net profit margin (NPM) dan earning per share (EPS) terhadap return saham dengan struktur modal sebagai variabel intervening - Vini Yuningsih (Universitas Widya Mataram, 2020)
This research belongs to the type of correlational research. The population in this study is the Property & Real Estate Services Company listed on the Stock Exchange in 2013-2017 which has a total assets of at least 10 trillion. To determine the sample, researchers use financial statement data. The research sample was obtained from financial data found at www.idx.com. The sample members used 7 companies in 5 periods. The data analysis technique used is data quality test, classic assumption test, multiple regression test, t test, determination test and path analysis test.